In Search of Shilan - River, Memuzin (Tribal Media Makers, 2008)
Verzio FF Submission Ten years ago, Cetin, a Kurdish poet, went into exile from Turkey and after many months, via Bulgaria and South Africa, arrived in Australia as a refugee. Leaving the Turkish army after witnessing atrocities committed in Kurdish villages, he put himself in danger by publicizing the army’s actions, and in doing so was forced to leave the woman he loved. Now, he wants to find Shilan, his lost love. He has never forgotten her, never married during his life in Australia. Shilan however has undergone some changes: she has become a guerrilla soldier in the PKK, living in the remote Zagros Mountains of northern Iraq and Iran, and has dedicated herself to the struggle to re-establish a Kurdish homeland. Ten years on, the situation is reversed - this time it’s Shilan who has to choose between love for a man and love for her homeland.